Age Differences in the Quality of Chronic Pain: A Preliminary Study - Lucia Gagliese; Ronald Melzack (Pain Research and Management)
BACKGROUND: Recent studies of the relationship between age and the intensity of chronic pain report increases, decreases or no change in pain intensity as a function of age. These inconsistencies may be due in part to the pain assessment tools employed and their appropriateness with different age groups.